1974
DOI: 10.1128/jb.120.3.1339-1343.1974
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Biosynthesis in Rhodotorula glutinis

Abstract: It was determined that lycopene could be cyclized directly by Rhodotorula glutinis . It was also shown the the temperature effect (i.e., increased β-carotene synthesis in response to lower incubation temperatures) in R. glutinis was controlled by changes in enzyme concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
7

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 21 publications
1
29
0
7
Order By: Relevance
“…In R. rubra , this change was accompanied by an accentuated decrease in the percentages of torularhodin (from 51 to 7%) and of torulene + neurosporene (from 33 to 15%) with increasing DPA added to the culture medium. Hayman et al. (1974) also reported a decrease in the production of torulene by R. glutinis in the presence of DPA.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…In R. rubra , this change was accompanied by an accentuated decrease in the percentages of torularhodin (from 51 to 7%) and of torulene + neurosporene (from 33 to 15%) with increasing DPA added to the culture medium. Hayman et al. (1974) also reported a decrease in the production of torulene by R. glutinis in the presence of DPA.…”
Section: Resultsmentioning
confidence: 89%
“…Studies on the use of specific carotenoid‐biosynthesis inhibitors in Rhodotorula strains are rare. Carotenogenesis in Rhodotorula glutinis was evaluated using the cyclization inhibitor 2‐(4‐chlorophenylthio)‐triethylamine (Hayman et al. 1974), and the dehydrogenation inhibitors such as methyl‐heptanone, β‐ionone (Simpson et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can affect the propagation of carotenoid producers in general and influence the production of single carotenoid and carotenoid ratios along the biosynthesis pathway in specific. Hayman et al [34] reported that the relative concentrations of individual carotenoids produced by R. glutinis were different when cultivated at 4°C and 25 °C, respectively. Similar results were observed in another strain of R. glutinis, 48-23T, in which the composition of carotenoids varied when different culture temperatures were applied.…”
Section: Optimization Approaches On Cultivation Conditions For the Prmentioning
confidence: 99%
“…Several bacteria, fungi and yeasts are good carotenoid producers (Johnson and Schroeder 1995). Of the yeasts, those species belonging to the genera Rhodotorula, Rhodosporidium, Sporobolomyces and Phaf®a have been known to form carotenoids from both synthetic and raw substrates for a long time (Mrak et al 1949;Nakayama et al 1954;Hayman et al 1974;Nelis and De Leenheer 1991;Vandamme 1992;Martin et al 1993;Frengova et al 1994;Johnson and Schroeder 1995;Shih and Hang 1996).…”
Section: Introductionmentioning
confidence: 99%